Fractal flow model for cluster interfacial nanolayer of magnetized metallic oxides nanomaterials. (December 2022) - Qureshi, M. Zubair Akbar; Raza, Qadeer; Darab, Pompei C.; Siddique, Imran; Fatima, Rameen; Ali, Bagh; Sallah, Mohammed
Abstract: In this paper, we investigate the novel properties of the cluster interfacial nanolayer theory for a thermal conductivity-based model. Under the influence of magnetohydrodynamics, the interaction of nanomaterials aggregation of metallic oxide nanomaterials with base fluid is explored. This paper discusses a specific form of new low permeability Reynolds number connected with an injection/suction factor related to an absorbent channel. A numerical simulation of higher-order nonlinear differential equations reveals the momentum flow and energy fields predicted by single-phase nanofluid simulations. Shear stress and Nusselt numbers were used to determine the effect of nanoparticle radius and diameter. Insertion of the metallic nanoparticles volume fraction level from 1% to 8% enhances the thermal performance at lower and upper porous walls respectively. Injection/suction and MHD have to decrease and increase behavior respectively in the presence of spherical nanoparticles. Interfacial nanolayer formation has a substantial impact on thermal conductivity performance. Comparing calculated findings to published literature validates their correctness. Graphs are generated to analyze the impact of flow parameters on velocity and temperature profiles. In tabular and graphical style, the effects of all physical factors are explored on the skin friction coefficient and the local Nusselt number.